Effects of an exercise program with augmented reality on functional fitness and physical activity of community-dwelling older adults - Ferreira, Soraia; Marmeleira, José; Del Pozo Cruz, Jesus; Leite, Nilton; Bernardino, Alexandre; Moradell, Ana; Raimundo, Armando (Frontiers in Sports and Active Living, 2025)
BackgroundThis study aims to investigate the effects of a multimodal program using augmented reality on the functional fitness and physical activity of older adults living in the community.MethodSeventy-eight older adults living in the community participated in this study. Participants were divided into three groups: a control group that maintained their usual activities, and two experimental groups, one with multimodal training (EG1) and the other with multimodal training combined with augmented reality (EG2). Participants were assessed at baseline and post-intervention, after 12 weeks. Functional fitness was assessed using the Rikli and Jones Senior Fitness Test, handgrip strength, the functional reach test, and the Fullerton Advanced Balance Scale. Physical activity was measured using accelerometry.ResultsIn EG1, lower limb flexibility, agility, cardiorespiratory fitness, and balance improved significantly between baseline and the 12-week outcome (p ≤ 0.001 for all). In EG2, improvements were observed in upper and lower limb strength, lower limb flexibility, agility, cardiorespiratory fitness, handgrip strength, and balance (p < 0.05 for all). Sedentary behavior increased in EG1 after the intervention. The clinical effect sizes of the interventions were large for balance (ES = 1.19) in EG1 and for upper limb strength (ES = 1.24) in EG2, and medium for cardiorespiratory fitness (ES = 0.74), agility (ES = 0.50), and lower limb flexibility (ES = 0.65) in EG1, and lower limb strength (ES = 0.61) and cardiorespiratory fitness (ES = 0.79) in EG2.ConclusionBoth intervention programs led to improvements in several functional domains. However, the multimodal training combined with augmented reality program showed improvements across more domains, resulting in greater changes. Physical activity did not show significant improvements.